2020
DOI: 10.1007/s00432-020-03429-x
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of microRNA-371a-3p are not elevated in testicular tumours of non-germ cell origin

Abstract: Purpose Serum levels of microRNA-371a-3p (M371) have been shown to be a highly sensitive and specific biomarker for testicular germ cell tumours (TGCT). Little information exists on the expression of this marker in testicular neoplasms deriving from the gonadal stroma or other structures of the gonad. This study presents an expression analysis of the novel TGCT-biomarker M371 in a large cohort of testicular non-germ cell tumours. Methods The M371 expression was measured by quantitative real time PCR in serum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 32 publications
3
18
0
3
Order By: Relevance
“…Importantly, for small benign tumors, partial orchiectomy may be an option, allowing to spare fertility and function of the testis (54). A large study already reported that such masses are negative for hsa-miR-371a-3p by RT-qPCR (55), and we show the same by ddPCR approach. Additionally, our assay has proved to be useful in clarifying elevations of AFP due to causes other than TGCTs, as has been recently reported for RT-qPCR (56).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Importantly, for small benign tumors, partial orchiectomy may be an option, allowing to spare fertility and function of the testis (54). A large study already reported that such masses are negative for hsa-miR-371a-3p by RT-qPCR (55), and we show the same by ddPCR approach. Additionally, our assay has proved to be useful in clarifying elevations of AFP due to causes other than TGCTs, as has been recently reported for RT-qPCR (56).…”
Section: Discussionsupporting
confidence: 68%
“…Since the study of Voorhoeve et al in 2006 (12), an overwhelming amount of evidence has been built in the last decade, demonstrating the accuracy of hsa-miR-371a-3p, determined by real-time quantitative PCR (RT-qPCR), for the diagnosis and follow-up of TGCT patients [except for pure teratoma (13)], with sensitivities and specificities of mostly >90% (14)(15)(16)(17). This microRNA has a short half-life, correlates with tumor burden, can be reliably detected in several bodily fluids, and is able to predict recurrences and viable tumor in post-chemotherapy masses (18)(19)(20)(21)(22)(23)(24)(25)(26)(27). The confirmation of these findings in large, prospective, multicentric studies increased even more the interest in this biomarker (28,29), leading to organization of clinical trials (NCT03067181 and NCT04435756) and proposals for introduction of a quantitative test in the clinic (30,31).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, we observed marker elevations in isolated patients with benign tumors, but there is no information about the extent of level elevations. This result is consistent with a previous series (Belge et al 2020 ). Most probably, these elevations represent idiopathic unspecific elevations similar to the AFP elevations in seminoma (Dieckmann et al 2017 ; Wymer et al 2017 ).…”
Section: Discussionsupporting
confidence: 94%
“…MicroRNAs of the miR-302/367 and miR371-373 clusters were found to be expressed in embryonal stem cells 16 and in testicular germ cell tumours 17 . Later, circulating microRNA-371a-3p (miR371) has been identified as the most promising candidate and shown to be present in almost all TGCC patients 17 23 . A large, prospective multicentre study showed miR371 to be positive in 90.1% of the TGCC cases at the time of diagnosis 20 .…”
Section: Introductionmentioning
confidence: 99%